Photometry and performance of SPECULOOS-South. Issue 2 (8th May 2020) - Murray, C A; Delrez, L; Pedersen, P P; Queloz, D; Gillon, M; Burdanov, A; Ducrot, E; Garcia, L J; Lienhard, F; Demory, B O; Jehin, E; McCormac, J; et al.
ABSTRACT: SPECULOOS-South, an observatory composed of four independent 1-m robotic telescopes, located at ESO Paranal, Chile, started scientific operation in 2019 January. This Southern hemisphere facility operates as part of the Search for Habitable Planets EClipsing ULtra-cOOl Stars (SPECULOOS), an international network of 1-m-class telescopes surveying for transiting terrestrial planets around the nearest and brightest ultracool dwarfs (UCDs). To automatically and efficiently process the observations of SPECULOOS-South, and to deal with the specialized photometric requirements of UCD targets, we present our automatic pipeline. This pipeline includes an algorithm for automated differential photometry and an extensive correction technique for the effects of telluric water vapour, using ground measurements of the precipitable water vapour. Observing very red targets in the near-infrared can result in photometric systematics in the differential light curves, related to the temporally-varying, wavelength-dependent opacity of the Earth's atmosphere. These systematics are sufficient to affect the daily quality of the light curves, the longer time-scale variability study of our targets and even mimic transit-like signals. Here we present the implementation and impact of our water vapour correction method. Using the 179 nights and 98 targets observed in the I + z ′ filter by SPECULOOS-South since 2019 January, we show the impressive photometric performance of the facility (with a median precision of ∼1.5 mmag for 30-min binning of the raw, non-detrended light curves) and assess its detection potential. We compare simultaneous observations with SPECULOOS-South and TESS, to show that we readily achieve high-precision, space-level photometry for bright, UCDs, highlighting SPECULOOS-South as the first facility of its kind.